MUNICIPAL CHANGES IN SLOVAKIA. THE EVIDENCE FROM SPATIAL DATA - MARIS, Martin (European Journal of Geography, 2022)
The main objective of the paper is to examine the evolution of spatial patterns of settlement network in Slovakia as a result of population rearrangement among municipalities based on time series data of 1993 - 2017. The objects of the research are municipalities, which during the searched period recorded unusual fast population growth or decline, far exceeding the chosen parameter of the population sample. The primary population sample consists of 2919 municipalities. The experimental samples consist of 563 of fast-growing municipalities and 413 of fast-declining municipalities, based on the chosen statistical criteria, what is the compound annual growth rate. The results have shown that fast-growing municipalities are predominantly situated on the West, surrounding the Bratislava agglomeration, on the North and the East surrounding the Kosice metropolis. Generally, they tend to cluster around the cities on the district and regional levels. Fast-declining municipalities predominantly situated in the Middle, along the Hungarian, Polish, and Ukrainian border on the South and the East of the country, respectively.